Influential mechanism of green consumption on the realization of ecological products value in China - Shao, Jingbo; Cai, Chengzhi (Frontiers in Sustainable Food Systems, 2025)
IntroductionRealizing the value of ecological products (EP) is of great significance to comprehensively promote the green transformation of China’s economy. With the increasing demand of consumers for green, environmental protection and health, the great tendency of people’s green consumption (GC) has been triggered. Based on the theory of sustainable development and the theory of ecosystem services, this paper constructs relevant econometric models and deeply discusses the influence mechanism of demand-side GC behavior on the Ep value realization (EPVR).MethodsThis paper obtains the reliability data from the relevant statistical reports and statistical yearbooks, and innovatively constructs the index system of EPVR and GC whose comprehensive indexes are measured by entropy weight TOPSIS method. In the data analysis stage, STATA software was used for unit root test, cointegration test, multicollinearity test and descriptive statistics. On this basis, regression analysis was carried out by constructing a two-way fixed effect model, mediating effect and moderating effect model.Results and discussion(1) The level of EPVR is generally not high with a national average of 0.156 in the study area. The GC level of the study area is significantly different and the national GC level is 0.311; (2) From the regression results of the econometric model, GC has a significant positive effect on the EPVR, and has passed a series of robustness tests; (3) From the analysis of the influential mechanism, GC further affects the EPVR by affecting the supply willingness of EP, the advancement of industrial structure and the rationalization of industrial structure. Among them, the willingness to supply EP has a partial mediating effect, the advancement of industrial structure has a complete mediating effect, and the rationalization of industrial structure has a masking effect; (4) From the perspective of heterogeneity analysis, it is found that the influence of GC on the EPVR is enhanced in turn in eastern, central and western regions of China through grouping regression and adjustment effect test, and the promotion effect is more obvious in areas with lower economic development level. This paper provides an important literature reference for the impact of GC on the EPVR in China.